Dynamics of interacting skyrmions in magnetic nano-track - Al Saidi, W. (2023)
Controlling multiple skyrmions in nanowires is important for their implementation in racetrack memory or neuromorphic computing. Here, we report on the dynamical behavior of two interacting skyrmions in confined devices with a comparison to a single skyrmion case. Although the two skyrmions shrink near the edges and follow a helical path, their behavior is different. Because the leading skyrmion is between the edge and the trailing one, its size is reduced further and collapses at a lower current density compared to the single skyrmion case. For higher current density, both skyrmions are annihilated with a core-collapse mechanism for the leading one followed by a bubble-collapse mechanism for the trailing one.